COVID-19 and its relationship with vulnerable populations - Aquino-Canchari, Christian Renzo (2020)
Introduction: Currently, it is worth reflecting on who is most vulnerable to pandemics. Although it is true that COVID-19 has the potential to impact everyone in society, it will be greater in vulnerable populations. Objective: To describe the relationship of COVID-19 in vulnerable populations. Material and Method: A bibliographic review was made from a total of 84 bibliographic references. Scientific articles in electronic format in English and Spanish were used; they were available from databases such as PubMed, Scopus, Medline, SciELO, and the Google Scholar search engine. Websites of the Ministries of Health, WHO, PAHO, INFOMED and national and international web pages were also explored. The quality, reliability and validity of the selected articles were analyzed to carry out an adequate review. Development: In the different vulnerable groups analyzed, the increased risk of contagion and the development of severe stages due to SARS-CoV-2 infection was evidenced. There is still no consensus regarding the management and treatment of COVID-19 in older adults, people with comorbidity and immunosuppressed.